The Feasibility of a Home Care Management Model Based Coaching Intervention on Indonesian Caregivers' Outcomes of Relatives with Schizophrenia - Purba, Jenny Marlindawani; Simamora, R H; Ginting, E D (Jurnal Keperawatan Soedirman, 2018)
Background. Caring for schizophrenia is a challenge and a burden for caregiver. In fact, family caregivers did not know how to care schizophrenia at home. A home management care base coaching is urgently needed. It can be used as a basis for nurses to assist caregivers in caring for persons with schizophrenia. Aims and Objectives. The study aimed to determine the feasibility of a home care management model base coaching for family caregivers of persons with schizophrenia.Methods. The study was two groups pre-test post-test quasi-experimental design. Thirty family caregivers were assigned into experimental and control group with each group 15 persons. Data were collected using the Chiang Mai Psychiatric Caregiving Scale, the Zarit Caregiver Burden Scale and the Schizophrenia Caregiver Quality of Life questionnaire. It was six weeks activities with several methods, such as discussion, watching videos, providing information, training, and home visit.Results:The participants who receive interventions reported significantly more improved in caregiving skills (p<0.05), increased quality of life (p < 0.05)and decreased the level of burden care (p<0.05) than those receiving the routine care.Conclusions:The study revealed that home care management model base coaching intervention was effective to improve caregivers’ outcomes in caring for relatives with schizophrenia.